Promotional Role of Microcredit: Evidence from the Grameen Bank of Bangladesh - Basher, M. Abul (2012)
This paper investigates whether the income augmenting role of microcredit is attributable only to increased participation of the borrower in economic activities or switch to more productive activities also. The paper provides a framework to analyze this question in absence of any longitudinal data. By using the data from the Grameen Bank of Bangladesh, the paper finds that microcredit enables the borrowers to move progressively into more productive activities as they become experienced.